Diversity and effect of the microbial community of aging horse manure on stable fly (Stomoxys calcitrans) fitness - Albuquerque, Thais Aguiar De (Kansas State University, 2012)
Stable flies (Stomoxys calcitrans L.) are blood-feeding insects with a great negative impact on livestock resulting in annual losses around $2 billion in the USA alone. One of the main reasons for such an impact is because stable fly management is very difficult. Stable fly larvae develop primarily in animal manure and live bacteria were shown to be essential for stable fly development. I hypothesized that the microbial community of horse manure changes over time and plays an important role in stable fly fitness. Two-choice bioassays were conducted using 2 week old horse manure (control) and aging horse manure (fresh to 5 week old) to evaluate the effect of manure age on stable fly oviposition. The results showed that fresh manure did not stimulate oviposition and that the attractiveness increased as manure aged but started to decline after 3 weeks. Stable fly eggs artificially placed on 1, 2, and 3 week old manure resulted in significantly higher survival and heavier adults comparing to those developing in fresh, 4, and 5 week old manure. Analysis of the bacterial community of aging horse manure by 454-pyrosequencing of 16S rDNA revealed a major shift from strict anaerobes (e.g. Clostridium, Eubacterium, Prevotella, Bacteroidales) in fresh manure to facultative anaerobes and strict aerobes (e.g. Rhizobium, Devosia, Brevundimonas, Sphingopyxis, Comamonas, Pseudomonas) in 1-5 week old manure. Identified volatile compounds emitted from 2 and 3 week old horse manure included phenol, indole, p-cresol, and m-cresol. However, none of them stimulated stable fly oviposition in two-choice assays. In conclusion, the microbial community of 2 and 3 week old horse manure stimulates stable fly oviposition and provides a suitable habitat for stable fly development. Manure at this stage should be the main target for disrupting the stable fly life cycle. Volatile compounds acting as oviposition stimulants/attractants and their specific bacterial origin remain to be determined. Better understanding of stable fly microbial ecology is critical for development of novel management strategies based on alteration of the microbial community of stable fly habitat to generate a substrate that is non-conducive to fly oviposition and/or larval development.
Keywords: Stomoxys calcitrans; Manure; Oviposition; Development; Bacteria; Stable fly; Entomology (0353)